Immunological study on some of Psoriatic Iraqi PatientsTreated with Etanercept - Abd-Alkhaliq, Ghufran Qasem; Abd, Wisal Salman (International Journal of Psychosocial Rehabilitation, 2020)
The present study is accomplished on (60) patients and (30) healthy individual. Serum levels of (Interleukin 17A (IL17A), Interleukin 17AR (IL17AR)and anticitrullinated protein antibody(ANTI-CCP) is estimated using Enzyme Linked Immunosorbent Assay (ELISA) technique and RF by latex test. Our results were high starting with IL17A mean value before treatment (967.24±784.1), IL17AR (818.62±647.33),ANTI-CCP (33.96±51.82) and with P value of (<0.0001). These levels were reduced significantly after treatment with (Etanercept) injection to give a mean levels of IL17A (360.61±302.38), IL17AR (118.67±191.85), ANTI-CCP (33.98±38.04) and with P value of (<0.0001).Patients were diagnosed with psoriasis arthritis (PsA) by calculating the degree of ANTI-CCP and results were 12 patients before treatment and 17 patients after treatment.ANTI-CCPwas important to diagnose PsA. IL17A, IL17AR have an important role in increasing the inflammation and as a marker for follow up after choosing a treatment in psoriasis and PsA.